Prevalence of renal dysfunction in tacrolimus‐treated pediatric transplant recipients: A systematic review. (28th February 2013) - Gijsen, Violette M. G. J.; Hesselink, Dennis A.; Croes, Kenneth; Koren, Gideon; de, Saskia N.
Abstract Renal dysfunction after non‐renal transplantation in adult tacrolimus‐treated transplant patients is well documented. Little is known about its prevalence in children. Age‐related changes in both disposition and effect of tacrolimus as well as renal function may preclude extrapolation of adult data to children. To systematically review the literature on renal dysfunction in non‐renal pediatric transplant recipients treated with tacrolimus. PubMed/Medline, Embase, and Google were searched from their inception until April 19, 2012, with the search terms "tacrolimus, " "renal function, " "transplantation, " and "children." Eighteen of 385 retrieved papers were considered relevant. Twelve dealt with liver, four with heart transplant, one with heart and lung transplant, and one with intestinal recipients. Reported prevalences of mild and severe chronic kidney disease ranged from 0% to 39% and 0% to 71.4%, respectively, for liver, and from 22.7% to 40% and 6.8% to 46%, respectively, for heart and/or lung transplant recipients. Ranges remained wide after adjusting for follow‐up time and disease severity. Possible explanations are inclusion bias and definitions used for renal dysfunction. A considerable proportion of pediatric non‐renal transplant patients who receive tacrolimus‐based immunosuppression, appear to suffer from chronic kidney disease. This conclusion warrants further research into the real risk, its risk factors, and individualization of immunosuppressant therapy.